2020
DOI: 10.1634/theoncologist.2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

When It Comes to Geriatric Assessment, Rome Was Not Built in One Day

Abstract: Opinions vary on the value of geriatric assessments prior to high‐risk therapy for older adults with cancer. This commentary focuses on whether the higher risk of poor outcomes for older patients with cancer can be mitigated by interventions aimed at detecting age‐related impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A randomized study showed that an evaluation before surgery led to a reduction in 90-day postoperative mortality. 79-81 Developing education programs for all oncology professionals is critical for optimal management of patients. 82,83…”
Section: Geriatric Oncology In Cancer Centersmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized study showed that an evaluation before surgery led to a reduction in 90-day postoperative mortality. 79-81 Developing education programs for all oncology professionals is critical for optimal management of patients. 82,83…”
Section: Geriatric Oncology In Cancer Centersmentioning
confidence: 99%
“…A randomized study showed that an evaluation before surgery led to a reduction in 90-day postoperative mortality. [79][80][81] Developing education programs for all oncology professionals is critical for optimal management of patients. 82,83 RECENT HISTORY OF GERIATRIC ONCOLOGY Since the 2014 special issue, the field has continued to develop with research and new investigators.…”
Section: Geriatric Oncology In Cancer Centersmentioning
confidence: 99%
See 1 more Smart Citation